Productivity, cation absorption and severity of alternaria potato influenced by potassium fertilization - Soares, Maria Elisa Paraguassu; Cavalcante, Alian Cássio Pereira; Andrade, Guilherme Antonio Vieira de; Barbosa, Iandra Rocha; Lima, Nelson Júnior Corrêa; Aquino, Leonardo Angelo de (Scientia Plena, 2020)
Potassium (K) is the nutrient most extracted by the potato crop and its deficiency drastically reduces productivity and increases early blight severity. Excessive K fertilization may reduce calcium (Ca) and magnesium (Mg) absorption and compromise productivity just as much as K deficiency. The influence of K fertilization on Ca, Mg and K absorption is not documented for Asterix potato grown in clay soil. The objective of this study was to evaluate the absorption and partitioning of K, Ca and Mg in the potato plant, in the productivity, and in the severity of early blight as a function of K2O doses. The treatments consisted of five doses of K: 0, 150, 300, 500, and 700 kg ha-1 of K2O. Doses were applied in two steps: 150 kg ha-1 of K2O in the planting groove together with the N and P and the remainder of each dose, with broadcast fertilization preceding the hilling process that took place 21 days after planting. Early blight severity and the number of small tubers decreased, while the number of large tubers increased as a function of K doses. The optimal dose for total productivity was 291.3 kg ha-1 of K2O. In addition, the absorption of Ca and Mg were reduced by high doses of K, which shows that the doses of this nutrient must be consistent with the extraction of the potato crop.